Hamka (1908-1981) and the Integration of the Islamic Ummah of Indonesia - Steenbrink, Karel (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
Islam is a unifying factor at the same time breaking in Indonesian history. Based on historical records, the conversion of Islam in Indonesia starts from kingdoms located in coastal areas. This conversion greatly benefit the kingdom, with which they can access a wider trade network which already controlled by Muslims. This conversion process can then unify the Malay traders origin, Java, and their other competitors. But with the entry of traders into the new religion beaches, hinterland connections with the merchant becomes tenuous. The situation may ultimately culminated into a dispute. In the Sumatra area, which is pretty much known example is the Padri war and the Islamization of the southern part of the Batak.DOI: 10.15408/sdi.v1i3.851